Pengaruh Kebijakan Dividen dan Umur Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas, Ukuran Perusahaan, dan Likuiditas sebagai Variabel Kontrol (Analisis pada Perusahaan Subsektor Farmasi Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2017-2 - Hakim, Aqil Lukmanul; Pratomo, Dudi (eProceedings of Management, 2024)
Company value refers to the perception of shareholders on the company's needs related to the value of shares.Company value aims to increase and create added value for investors or shareholders. The price of the shares tradedcan be an examination for investors to know the company's value. The high level of return to investors is influencedby the high stock price, if the stock price is lower, it tends to affect the low level of return to investors. This study aimsto examine the influence of dividend policy and company age on company value by using profitability, company size,and liquidity as a control variables in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchangein 2017-2022. The population in this study is companies engaged in the pharmaceutical sub-sector. By using asampling technique, namely purposive sampling, and has a total of 54 samples from 9 companies within 6 years. Paneldata regression is carried out by utilizing Eviews 12 software to process data. This study shows that dividend policiesand company age using profitability control variables, company size, and liquidity have a simultaneous effect on thecompany's value. Partially the dividend policy has no significant effect, and the age of the company has a significanteffect on the value of the company. Keywords-firm value, dividend policy, profitability, firm size, liquidity